Long waves of capitalist development: An empirical investigation - Deepankar Basu (University of Massachusetts, Department of Economics, 2016)
In this paper, I investigate the phenomenon of long waves of capitalist development from two perspectives. First, I look for evidence of long waves of economic growth taking the dates for turning points of long waves from the historical literature (Mandel, 1995). Using historical data for 20 capitalist countries from the Maddison-Project, I find that the growth rate of real per capita GDP (and real GDP) is significantly higher in the upswing than in the downswing phase of long waves. I interpret this as evidence of long waves of economic activity. Second, I revisit the method used by Gordon, Weisskopf and Bowles (1983) to identify long waves, using historical data on the U.S. economy from Duménil and Lévy (2013). I use this definition of long waves to test their hypothesis that business cycle downturns are "reproductive" during the upswing phase and "nonreproductive" during the downswing phase of long waves. I find evidence in support of the hypothesis.
Keywords: B14; B24; B51; 330; capitalism; long waves; expected profitability